1994
DOI: 10.1073/pnas.91.21.9700
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the VHL tumor-suppressor gene by DNA methylation in renal carcinoma.

Abstract: Mutational Inactivation and allelic loss of the von HlppelLlndau (VHL) gene appear to be causal events for the majority of spontaneous clear-cell renal cardnomas. We now show that hypermethylatlon of a normally unmethylated CpG Island in the 5' region provides another potentially important mechanism for Inactivation of the VHL gene In a siificant portion of these cancers. This hypermethylation was found in S of 26 (19%) tumors examined. Four of these had lost one copy of VHL while one retained two heavily meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
767
2
15

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,369 publications
(807 citation statements)
references
References 24 publications
23
767
2
15
Order By: Relevance
“…Thus, the epigenetic inactivation of HOXB13 is independent of the VHL status. This may help us to elucidate the tumorigenic mechanisms of RCCs that lack VHL inactivation, which constitute approximately 40% of the sporadic clear cell RCC cases (Foster et al, 1994;Gnarra et al, 1994;Herman et al, 1994;Shuin et al, 1994Shuin et al, , 1999. Notably, multivariate analysis of the clinicopathological parameters using a logistic regression model showed that HOXB13 methylation correlated significantly with tumor grade and microvessel invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the epigenetic inactivation of HOXB13 is independent of the VHL status. This may help us to elucidate the tumorigenic mechanisms of RCCs that lack VHL inactivation, which constitute approximately 40% of the sporadic clear cell RCC cases (Foster et al, 1994;Gnarra et al, 1994;Herman et al, 1994;Shuin et al, 1994Shuin et al, , 1999. Notably, multivariate analysis of the clinicopathological parameters using a logistic regression model showed that HOXB13 methylation correlated significantly with tumor grade and microvessel invasion.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 30 000 newly diagnosed cases in the USA and 7000 occur in Japan every year. Previous studies revealed that the von Hippel-Lindau (VHL) gene is the major tumor suppressor gene that participates in the development of human RCC, as it is inactivated, mostly by genetic alterations, in about 60% of sporadic RCC cases (Foster et al, 1994;Gnarra et al, 1994;Herman et al, 1994;Shuin et al, 1994Shuin et al, , 1999. However, the tumorigenic mechanisms for the sporadic RCCs that lack VHL gene inactivation and the multi-step processes involved in RCC progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The response of metastatic RCC to conventional chemotherapy is poor, but characterisation of the molecular pathology of RCC can provide a basis for developing novel therapeutic approaches. This is exemplified by the VHL TSG paradigm in which (a) inactivation of VHL is the most common event in sporadic clear cell RCC (Latif et al, 1993;Foster et al, 1994;Herman et al, 1994;Clifford et al, 1998); (b) VHL inactivation leads to stabilisation of HIF-1 and HIF-2 transcription factors and activation of hypoxic response genes that drive renal tumourigenesis (Maxwell et al, 1999); and (c) inhibitors (for example, tyrosine kinase inhibitors such as sorafenib and sunitinib) of HIF target pathways are active in the treatment of metastatic RCC (Chowdhury et al, 2008). Hence, identification of frequently inactivated RCC TSGs can provide a basis for novel therapeutic interventions.…”
Section: Ct Bstu1mentioning
confidence: 99%
“…Anomalies within the p53 tumor suppressor gene are not common in RCC. Mutations in the Von Hippel-Lindau (VHL) tumor-suppressor gene (Latif et al, 1993;Herman et al, 1994;Iliopoulos et al, 1995) or amplification and activation of the tyrosine kinase c-Met (Schmidt et al, 1997;Fischer et al, 1998;Zhuang et al, 1998;Lubensky et al, 1999) have been shown to play critical roles in the development of some RCCs. Despite these advances, the full spectrum of molecular changes that occur in the tumor is far from clear.…”
Section: Introductionmentioning
confidence: 99%